Comparison of the Effectiveness of Topical 5-Fluorouracil, Topical Calcipotriol, and Liquid Nitrogen Cryosurgery in Seborrhoeic Keratosis - Sutedja, Eva Krishna; Suwarsa, Oki; Febrina, Dia; Wibowo , Raka Ghufran; Tasbun, Felix (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Seborrhoeic keratosis (SK) is a benign tumor composed of epidermal keratinocytes occurs most frequently in the elderly. The action of 5-fluorouracil (FU) cream and calcipotrienes on keratinocyte development and has been shown beneficial for SK. Purpose: To compare the effectiveness of 5-FU and calcipotriol topical with cryosurgery. Methods: Eighteen SK patients with 54 skin lesions were enlisted, which were separated into three groups. The first group received topical 5-FU twice daily, the second group received one 10-second freeze-thaw cycle of liquid nitrogen cryosurgery, and the third group received topical calcipotriol twice daily. The success of therapy was assessed based on the reduction in baseline lesion size, and observations were made every two weeks for three months. Result: This study found that at the 12th week, the mean percentage of decrease in lesion size in group I was 34.6%, group II was 100%, and group III was 6.18%. Statistically, there was a significant difference in the decrease in lesion size in groups treated with cryosurgery (p value<0.001). The most common side effect in group I was discomfort, whereas in group II it was hyperpigmentation. Patients from group III reported no negative effects. Conclusion: Topical 5-FU and topical calcipotriol are less effective than cryosurgery in SK in terms of reducing lesion size. However, topical 5-FU reduced the size of lesions more than topical calcipotriol.